PENGARUH IMBANGAN PROTEIN DAN ENERGI TERHADAP KUALITAS INTERIOR TELUR AYAM ARAB - Lestari, Rika Hari (Jurnal Sains dan Teknologi Industri Peternakan, 2024)
Arabic chicken has the advantage of easily adapting to Indonesia's tropical climate and resistance to disease, so that Arabic chicken has the potential to be cultivated in Indonesia. However, these advantages are still not enough to obtain quality eggs. This study aims to examine the effect of different protein and energy rations on improving the interior quality of Arabic chicken eggs, especially the yolk index, albumen index, Haugh Unit (HU) and Egg Yolk Color. This research was conducted for 6 weeks (36 days) and used 80 Arabic chickens aged 5 months. The ration composition consisted of yellow corn, bran, and RK 24 concentrate. The design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 10 replicates, namely R1 (15% protein and EM 2500 Kcal), R2 (16% protein and EM 2600 kcal), R3 (Protein 17 % and EM 2700 kcal) and R4 (Protein 18 % and EM 2800 kcal). The results showed that the treatment had no significant effect (P>0.05) on the yolk index, albumen index and Haugh Unit (HU). However, it had a significant effect (P<0.05) on the color of the Arabic chicken egg yolk. As the energy and protein balance of the ration increases, the resulting egg yolk color also increases. The conclusion in this study was that the energy balance of 2800 kcal and 18% protein produced the highest egg yolk color.